2019
DOI: 10.1136/bmjopen-2018-024609
|View full text |Cite
|
Sign up to set email alerts
|

Association between adverse childhood experiences and adult diseases in older adults: a comparative cross-sectional study in Japan and Finland

Abstract: ObjectiveWe aimed to examine the association between adverse childhood experiences (ACEs) and diseases in older adults in Japan and Finland.DesignCross-sectional comparative study.SettingData from a gerontological study in Japan and two public health studies in Finland were evaluated.ParticipantsA total of 13 123 adults (mean age, 69.5 years) from Japan and 10 353 adults (mean age, 64.4 years) from Finland were included in this study. Logistic regression was used to examine the association of each of, any of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 43 publications
5
25
0
Order By: Relevance
“…Adverse childhood experiences (ACE) can have profound effects on individuals of all ages [1][2][3]. Multiple studies have demonstrated that a history of adverse experiences during childhood and adolescence is linked with risky health behaviors [4][5][6] and many mental and physical health problems [3,7,8] well into adulthood [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Adverse childhood experiences (ACE) can have profound effects on individuals of all ages [1][2][3]. Multiple studies have demonstrated that a history of adverse experiences during childhood and adolescence is linked with risky health behaviors [4][5][6] and many mental and physical health problems [3,7,8] well into adulthood [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, recent research using a cohort study of independent adults older than 65 years in Japan 25,26 has shown that childhood maltreatment can lead to deteriorating health in late adulthood, including greater higher-level functional limitations and greater risk of diseases such as diabetes and hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, ACEs have been found to cause disadvantageous health-behavioral strategies in adulthood leading to smoking, higher alcohol consumption, drug abuse and risky sexual behavior [ 4 , 18 20 ]. It is evidentially outlined that poor mental well-being and low socio-economic status (SES), including low parental education and income, are potential risk factors for reporting ACEs [ 5 , 14 , 21 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Denmark. To our knowledge, no previous studies investigating the association between ACEs and SRH in Denmark have been conducted and only two studies from Scandinavia were found [ 21 , 26 ]. Overall, the current evidence on the association between ACEs and SRH are dominated by cross-sectional studies studying elderly populations using a retrospective approach to collect information on ACEs, and the majority of these studies suffer from a risk of both survival- and information bias.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation